2011
DOI: 10.1002/ejoc.201001501
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic Synthesis of Phosphonic Acid Analogues of L‐Lysine, L‐Proline, L‐Ornithine, and L‐Pipecolic Acid of 99 % ee – Assignment of Absolute Configuration to (–)‐Proline

Abstract: (Ϯ)-ω-Halo-α-(chloroacetoxy)phosphonates were kinetically resolved by use of a protease (Chirazyme ® P-2). The esters recovered at levels of conversion between 56 and 72 % furnished (S)-alcohols of 99 % ee. These were converted via azides into the phosphonic acid analogues of L-lysine, L-pro-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Although a lower asymmetric induction was observed with this acylating agent, it permitted the straightforward synthesis of pipecolic phosphonic acid 9 by hydrogenation and phosphonate hydrolysis. Consequently, the absolute configuration ( S ) was determined by comparison of the optical rotation with the reported literature …”
Section: Figurementioning
confidence: 99%
“…Although a lower asymmetric induction was observed with this acylating agent, it permitted the straightforward synthesis of pipecolic phosphonic acid 9 by hydrogenation and phosphonate hydrolysis. Consequently, the absolute configuration ( S ) was determined by comparison of the optical rotation with the reported literature …”
Section: Figurementioning
confidence: 99%
“…For the synthesis of the enantiomers of phosphaaspartic acid and phosphaarginine, the enantiomers of diisopropyl 1‐hydroxy‐3‐butenylphosphonate were needed. In order to obtain them with a high ee , the racemate was resolved by enzyme‐catalyzed hydrolysis of the respective chloroacetate . Therefore, the α‐hydroxyphosphonate (±)‐ 6 was chloroacetylated with chloroacetic anhydride and pyridine (see Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…We tested a series of lipases (SAM I and II, AP 6, FAP 15, SP 523, Chirazyme L9, and from Candida antarctica, Candida cylindracea , and Thermomyces lanuginosus ) and found that the lipase from Thermomyces lanuginosus was best (Scheme ). Briefly, chloroacetate (±)‐ 7 was hydrolyzed in a vigorously stirred biphasic system of phosphate buffer pH 7.0 and organic solvent (hexanes/ t BuOMe, 1:1) by the lipase from Thermomyces lanuginosus by using an autotitrator to add 0.5 m NaOH to maintain the pH constant at 7.0 . When 40 % of the substrate, based on the consumption of 0.5 m NaOH, had been hydrolyzed, the mixture was extracted with EtOAc.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations